(3edLC GdbVGI YfO JYGQV GdHjfGJs - (3GdHZOGOj, CHh eMeO, ZjGK GdOjf, ZGfe Hf eMeO, J(B1030(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; SHMGf ef dG MLI Cbhi ef cdGeg hHYO ajbhd GdYHO GdabjQ Edi GdZfj ZGfe Hf eMeO GdHZOGOj , gPg QSGdI aj JYGQV GdHjfGJ LeYJgG dHYV ENhGfj ef GdbVGD hSejJg edLCI GdbVGI YfO JYGQV GdHjGfJs
(3BNQgG (B:s
(3hEf cGfJ GdeSFdI ef ZjQ XGgQGf cGf jhGab CUhd CUMGHfG jYed HgeG hCf de jLO dgG QhGjI Yf CUMGHgG hGJab ajgG GdeJCNQhf Ydi TjA jYed Hg hEf GNJdahG jLJgO hjaJj HeG gh UhGH YfOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 116s
(3eYLe GdeDdajf (B2 / 602s
(3cTa GdXfhf (B2 / 1846s
(3gOjI GdYGQajf (B1 / 812s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs